2011
DOI: 10.1007/s11095-011-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Topical and Transdermal Delivery of Antineoplastic and Antiviral Acyclic Nucleoside Phosphonate cPr-PMEDAP

Abstract: Transdermal or topical application of cPr-PMEDAP enabled by the permeation enhancer DDAK may provide an attractive alternative route of administration of this potent antitumor and antiviral compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Then, after reaching enzymatically active nucleated epidermis, its labile bond could be hydrolyzed, thus releasing known non-toxic compounds with much lower irritation potential. This approach to designing permeation enhancers resulted in the identification of highly potent enhancers with favorable properties, such as DDAIP [16], Transkarbam 12 (T12, [23,24]), tranexamic acid derivatives [25], and dodecyl 6-(dimethylamino)hexanoate (DDAK, [26][27][28], Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Then, after reaching enzymatically active nucleated epidermis, its labile bond could be hydrolyzed, thus releasing known non-toxic compounds with much lower irritation potential. This approach to designing permeation enhancers resulted in the identification of highly potent enhancers with favorable properties, such as DDAIP [16], Transkarbam 12 (T12, [23,24]), tranexamic acid derivatives [25], and dodecyl 6-(dimethylamino)hexanoate (DDAK, [26][27][28], Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…64 Transdermal and topical delivery of cPrPMEDAP was recently described. 65 The enzyme responsible for the conversion of cPrPMEDAP to PMEG was shown to be an hitherto unknown N 6 -methyl-AMP aminohydrolase. 66 GS-9191 has been further pursued for its utility in the topical treatment of HPV-associated lesions such as genital warts.…”
Section: Q Gs-9191mentioning
confidence: 99%
“…The antitumor potential of cPrPMEDAP was demonstrated in a choriocarcinoma model in rats . Transdermal and topical delivery of cPrPMEDAP was recently described . The enzyme responsible for the conversion of cPrPMEDAP to PMEG was shown to be an hitherto unknown N 6 ‐methyl‐AMP aminohydrolase .…”
Section: Introductionmentioning
confidence: 99%
“…1) (13,14). This amino acid-based penetration enhancer increased skin flux of the structurally related ANPs adefovir by 179-fold (14,15) and cPr-PMEDAP by 61-fold (13). Furthermore, DDAK increased skin flux of theophylline by 17-fold, hydrocortisone by 43-fold, and indomethacin by 9-fold (16).…”
Section: Introductionmentioning
confidence: 95%
“…We have recently shown that certain enhancers can increase the absorption of ANPs by two orders of magnitude; one such enhancer is the amino acid derivative DDAK (dodecyl ester of 6-(dimethylamino)hexanoic acid, Fig. 1) (13,14). This amino acid-based penetration enhancer increased skin flux of the structurally related ANPs adefovir by 179-fold (14,15) and cPr-PMEDAP by 61-fold (13).…”
Section: Introductionmentioning
confidence: 99%